Targeted agents and immunotherapies: optimizing outcomes in melanoma - Luke, Jason J.; Flaherty, Keith T.; Ribas, Antoni; Long, Georgina V. (Nature reviews. Clinical oncology, 2017)
Key Points Clinical therapeutics for advanced-stage melanoma have improved dramatically with the development of BRAF and MEK inhibitors, cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) and programmed cell-death protein 1 (PD-1) blocking antibodies, and a modified oncolytic herpes virus that is delivered intratumourally The overall survival of patients with advanced-stage melanoma has improved from ∼9 months before 2011 to an as yet undefined timeframe, with a subset of patients having ongoing long-term tumour control Melanoma, particularly cutaneous melanoma, is amendable to immunotherapy for various reasons, including extensive tumour infiltration by T cells, a high mutational load, and crosstalk between oncogenic signalling pathways and immunobiology Resistance mechanisms to BRAF-targeted treatments and immunotherapies are being elucidated; reactivation of the MAPK pathway is common after BRAF inhibition, whereas the effectiveness of both approaches might be limited by loss of tumour antigen presentation and T-cell trafficking To move the field of clinical therapeutics forward, a greater focus on specific patient populations (based on serum lactose dehydrogenase levels, ECOG performance status, and number of metastases), as well as on landmark progression-free and overall survival measures, will be required in clinical trials In less than a decade, the treatment landscape of metastatic melanoma has changed dramatically. Novel targeted agents and immunotherapies are revolutionizing patient outcomes, but the range of available drugs complicates clinical decision-making. Herein, the authors chart the therapeutic advances and review the current evidence that can be used to guide therapeutic decisions for individual patients with metastatic melanoma, highlighting knowledge gaps. Treatment options for patients with metastatic melanoma, and especially BRAF -mutant melanoma, have changed dramatically in the past 5 years, with the FDA approval of eight new therapeutic agents. During this period, the treatment paradigm for BRAF -mutant disease has evolved rapidly: the standard-of-care BRAF-targeted approach has shifted from single-agent BRAF inhibition to combination therapy with a BRAF and a MEK inhibitor. Concurrently, immunotherapy has transitioned from cytokine-based treatment to antibody-mediated blockade of the cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) and, now, the programmed cell-death protein 1 (PD-1) immune checkpoints. These changes in the treatment landscape have dramatically improved patient outcomes, with the median overall survival of patients with advanced-stage melanoma increasing from approximately 9 months before 2011 to at least 2 years — and probably longer for those with BRAF -V600-mutant disease. Herein, we review the clinical trial data that established the standard-of-care treatment approaches for advanced-stage melanoma. Mechanisms of resistance and biomarkers of response to BRAF-targeted treatments and immunotherapies are discussed, and the contrasting clinical benefits and limitations of these therapies are explored. We summarize the state of the field and outline a rational approach to frontline-treatment selection for each individual patient with BRAF -mutant melanoma.